2023
DOI: 10.1177/03635465221141876
|View full text |Cite
|
Sign up to set email alerts
|

Elevated In Vivo ACL Strain Is Associated With a Straight Knee in Both the Sagittal and the Coronal Planes

Abstract: Background: Noncontact anterior cruciate ligament (ACL) injuries typically occur during deceleration movements such as landing or cutting. However, conflicting data have left the kinematic mechanisms leading to these injuries unclear. Quantifying the influence of sagittal and coronal plane knee kinematics on in vivo ACL strain may help to elucidate noncontact ACL injury mechanisms. Purpose/Hypothesis: The purpose of this study was to measure in vivo sagittal and coronal plane knee kinematics and ACL strain dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 79 publications
2
1
0
Order By: Relevance
“…We believe that our previous work using imaging techniques to quantify in vivo ACL elongation and joint motion supports the findings of the present study, in that the previous studies suggested that knee extension elevates ACL strain 2-6,8,9,22-24 and puts the ligament at increased risk for injury. As noted previously, these techniques have advantages over cadaveric studies, which may not accurately reproduce in vivo loading conditions, 7 and videographic techniques, which may be susceptible to errors due to the viewpoint of the camera 3 and skin motion artifact.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We believe that our previous work using imaging techniques to quantify in vivo ACL elongation and joint motion supports the findings of the present study, in that the previous studies suggested that knee extension elevates ACL strain 2-6,8,9,22-24 and puts the ligament at increased risk for injury. As noted previously, these techniques have advantages over cadaveric studies, which may not accurately reproduce in vivo loading conditions, 7 and videographic techniques, which may be susceptible to errors due to the viewpoint of the camera 3 and skin motion artifact.…”
Section: Discussionsupporting
confidence: 90%
“…15 Specifically, this study suggested that the knee was in a straight position in both the sagittal (\20°of flexion) and coronal (\10°of valgus) planes and underwent large anterior tibial translation (.20 mm) near the time of ACL rupture for both bone bruise patterns. 15 We believe that our previous work using imaging techniques to quantify in vivo ACL elongation and joint motion supports the findings of the present study, in that the previous studies suggested that knee extension elevates ACL strain [2][3][4][5][6]8,9,[22][23][24] and puts the ligament at increased risk…”
Section: Discussionsupporting
confidence: 86%
“…Those studies found that the ACL elongation increased during knee extension and decreased during flexion. The same pattern of ACL elongation was observed in more demanding activities, such as a single‐leg hop test [12] and the double‐legged drop jump [9, 29]. However, in fast running, ACL relative elongation increased during knee flexion immediately after foot strike and decreased during knee extension [29].…”
Section: Discussionmentioning
confidence: 72%